Investigation of voice disorders and recognising the speech of children with hearing impairment in classical Tamil language. (2015) - Jeyalakshmi, C.; Revathi, A.; Krishnamurthi, V.
Speech from the hearingimpaired persons is highly disordered like dysarthric speech, according to their degree of hearing loss. A continuous speech recognition system for the hearingimpaired in Tamil language has been developed using a short vocabulary and it produces a recognition accuracy of 84.0%. It utilises the alphabet model instead of the phoneme model which improves the recognition rate reasonably. The developed speech recognition system can readily recognise the unintelligible speech and display that into normal text. This can be a very useful assistive device for the hearingimpaired to communicate with their normal peers and to operate all voiceoperated devices for command and control applications. Evaluation is also made to compare human and machine recognition accuracy, using ten isolated digits. It shows that, the overall accuracy is 26% by human compared to that of 92.4% by machine, which emphasises the need for the development of our computerbased speech recognition system.